Hospitalization Expenditures and Out-Of-Pocket Expenses in Patients With Stroke in Northeast China, 2015–2017: A Pooled Cross-Sectional Study - Ma, Zihua; Deng, Gongman; Meng, Zhaolin; Wu, Huazhang (Frontiers in Pharmacology, 2021)
Background: Stroke is the second most common cause of mortality worldwide and the leading cause of death in China. It imposes a heavy financial burden on patients, especially for some social groups that are vulnerable to economic risks. Objective: This study aimed to comprehensively assess the magnitude of hospital and out-of-pocket (OOP) costs associated with stroke in Northeast China. Methods: Patients were selected via a multistage stratified cluster random sampling approach. We reviewed all patients’ records from 39 hospitals across six cities in Liaoning Province between 2015 and 2017. Cost characteristics of four major stroke types were analyzed. Multivariate linear regression analyses were employed to examine the determinants of hospitalization costs and OOP expenses. Results: A total of 138,757 patients were assessed for the medical costs. The mean hospitalization costs were $1,627, while the mean OOP expenses were $691, accounting for 42.5% of the total expenditures. Medication expenses were the largest contributor to hospitalization costs. The regression analysis suggested that age, length of stay (LOS), social identity, type of stroke, surgery, intensive care unit (ICU) admission, hospital level and hospital type were significantly correlated with hospitalization costs and OOP expenses. Conclusions: Stroke imposes a heavy financial burden on both patients and society in Liaoning Province, Northeast China. Results showed that there are some differences in the individual and social economic burden among different types of stroke. In addition, stroke patients share a high proportion of costs through OOP expenses, especially for poor social-economic status patients. Targeted intervention measures and specific policies are needed to reduce the individual and social economic burden of stroke as well as improve equity in health care among different social groups.